Derangement in renal function after stoma creation in a tertiary care centre - Bagre, Rajendra; Gupta, Ayush; Kumar, Ritesh; Srinivas, Vinay; Kumar, Naveen; Kumar, Nitish (International Surgery Journal, 2024)
Background: We assessed the derangements of renal functions and glomerular filtration rate (GFR) due to dehydration and poor nutrition in stoma patients before the creation of stoma, on discharge and on readmission (closure/complication). Methods: We conducted a retrospective cohort study in 50 patients of both sexes of age group 16-80yr undergoing stoma formation either as an emergency or elective procedure. Changes in levels of urea, creatinine and GFR were checked preoperatively, on discharge and on follow up within 3 months. Diet of the patient, possibility of sepsis and other treatment including nephrotoxic drug treatment history was assessed. Results: Fifty patients including 27 males and 23 females of age group 16-75yr were included in this study. The most common stoma was loop ileostomy in 32 cases followed by double barrel ileostomy in 11 cases. Ileal perforation and ileal stricture are the 2 most common causes of stoma formation and 78% of stoma were made as an emergency procedure. We found that 56% of the cases presented with deranged renal functions and GFR on readmission. Conclusions: Deranged GFR was due to dehydration by high output and poor intake leading to renal injury and deranged renal functions. Proper counselling of the patient regarding nutritious diet, refeeding and adequate hydration is important to prevent renal failure in stoma patient.